PENINGKATAN HASIL BELAJAR MENGGIRING BOLA PADA PERMAINAN SEPAKBOLA MELALUI PENDEKATAN BERMAIN PADA SISWA SEKOLAH DASAR - Aditya, Rinaldi (STOK BINA GUNA MEDAN, 2017)
The aim of this action research is to improved learning result dribble  football games through approach playing for physical education.  In addition, this reaserch was conducted to obtain information about: application with the patterns approach playing for grade VI elementary school, and knowing the effectiveness, efficiency and improved learning results of dribble for physical education for grade VI elementary school. the design of this action research was using approach qualitative research methods. While the subjects in this reseach were 30 studentd grade VI elementary school 112146 janji on north sumatera.In testing the efffectiveness of the patterns approach playing can be see from the psychomotor data and resutl of dribble football games. The testing of learning result previos teaching (pree-test) was 30% of the expected criteria. While the effectiveness level of cycle I approach playing of football was 70% of the expected criteria. The next, continued approach playing of football games, the effectiveness level of cycle II was 86% of the expected criteria, it meant that there was an increase of 66%.Based on this research, it can be concluded that: (1) with the pattern approach playing for physical education, students can learn effectively and efficiently and Improved learning results of dribble (2) with the pattern approach playing, students more motivated as well as active in following the process of learning.